Chapter Vector-Borne Infections in Bulgaria - Christova, Iva (InTechOpen, 2019)
Bulgaria is an endemic country for Lyme borreliosis and Crimean-Congo hemorrhagic fever (CCHF). Sporadic cases of tick-borne encephalitis (TBE) and West Nile virus (WNV) encephalitis have been also reported. The reported incidence of Lyme borreliosis in Bulgaria is about 6/100,000 population. Two peaks in the seasonal distribution of cases and more frequent presentation of neuroborreliosis than of Lyme arthritis appear to be characteristics of Lyme borreliosis in Bulgaria. Borrelia afzelii is highly prevalent in Bulgarian Ixodes ricinus ticks. With sporadic cases or small outbreaks, CCHF appeared every year since the 1950s. For the last 10 years, a total of 60 CCHF cases were officially recorded. There is a tendency for CCHF to spread in previously non-endemic areas. The strains causing CCHF in the country belong to lineage Europe 1. A mean of 3.7% CCHF seroprevalence among the Bulgarian population is established. Both Europe 1 and Europe 2 CCHF virus lineages are present in ticks in Bulgaria. Tick-borne encephalitis (TBE) is very unusual. Only a few cases of TBE have been detected. Overall seroprevalence of 0.6% for TBE virus was found in humans. In 2015, a few WNV human cases were detected caused by lineage 2. Overall WNV seroprevalence in human population in the country is 1.5%.